Canonical strategies of Latin American poetic neo-baroque (Revista de Crítica Literaria Latinoamericana, 2012)
This article is a critical reading of the prefaces, proses and paratexts of the poetry anthologies Caribe transplatino (1991), Transplatinos (1991) and Medusario (1996) along with essays in Resistir (2004) by Eduardo Milán. It interprets how the neo-baroque movement of the late twentieth-century Hispanic poetry takes place in the literary field of poetry through the exclusion of formalism and conversational and political poetry. Thus the neo-baroque tries to take the place of the avant-garde, but also shows its modern notion of historicity, linear and progressive.
Keywords: neo-barroque; anthologies; paratexts; formalism; history